The Legal Prohibition Of Surrogacy For Muslims In Malaysia: A Critical Analysis (UUM Journal of Legal Studies, 2015)
This paper sets out to determine the legal status of human reproductive surrogacy for Muslims in Malaysia. It asks whether or not Muslims are prohibited by Islamic Law from human reproductive surrogacy. Muslims are governed in their personal matters by the Islamic law of the respective states. The word Muslim is not defined in the Malaysian Constitution. Argument deals with the position of the Islamic law in Malaysia, before discussing surrogacy. This will be set out first in the position of the Islamic law, then, argument discusses the role of the Islamic jurist and the Islamic legal consultative committee. This is followed by the role of the national fatwa committee. Finally, the article deals with the prohibition of surrogacy for Muslims as a legal dilemma. The paper will suggest that in some states, Muslims would be free to use surrogacy services in accordance with the general law of Malaysia. Keywords:Surrogacy, Surrogate mother, Surrogacy in Malaysia, Surrogacy in Islam